Recent Advances in Molecular Diagnostics of Fungal Plant Pathogens: A Mini Review - Hariharan, Ganeshamoorthy; Prasannath, Kandeeparoopan (Frontiers in Cellular and Infection Microbiology, 2021)
Phytopathogenic fungal species can cause enormous losses in quantity and quality of crops and this becomes increasingly a major economic menace to the global agricultural sector. Precise and rapid detection and identification of plant infecting fungi are ultimately essential to facilitate effective management of the diseases they cause. DNA-based methods now become popular methods for accurate plant disease diagnostics. Recent developments in standard and variant polymerase chain reaction (PCR) assays including nested, multiplex, quantitative, bio and magnetic-capture hybridization PCR techniques, post and isothermal amplification methods, DNA and RNA based probe development, and next-generation sequencing provide novel tools in molecular diagnostics in fungal detection and differentiation fields. These molecular based detection techniques are promising to detect symptomatic and asymptomatic diseases of both culturable and unculturable fungal pathogens in sole and co-infections. Even though the molecular diagnostic approaches have expanded substantially in the recent past still there is a long way to go in the development and application of molecular diagnostics in plant diseases. Molecular techniques used in plant disease diagnostics need to be reliable, faster, and easy to be used than conventional methods. Now the challenges are with the scientists to develop practical techniques to be used for molecular diagnostics of plant diseases. Recent advancement in the improvement and application of molecular methods for diagnosing the widespread and emerging plant pathogenic fungi are discussed in the review.